2013
DOI: 10.1186/2049-6958-8-26
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of cutaneous sarcoidosis; clinical and the prognostic significance of skin lesions

Abstract: BackgroundSarcoidosis is a systemic disease characterized by the formation of noncaseating granulomas in various tissues. Cutaneous involvement occurs in 20 to 35 percent of the patients and may be the initial manifestation of the disease. Our study was performed to discriminate the clinical, laboratory, and prognostic differences between patients with specific and nonspecific cutaneous involvement. The second aim was to asses the diagnostic usefulness of punch biopsy in sarcoidosis.MethodsThe clinical, labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 15 publications
1
10
0
2
Order By: Relevance
“…5 Clinical manifestations of systemic sarcoidosis are diverse (see Table 3) Approximately one-third of patients present with vague constitutional symptoms such as fatigue, fever, nights sweats, and weight loss. 102 Pulmonary sarcoidosis is clinically and pathologically the most common manifestation of the disease.…”
Section: Systemic Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Clinical manifestations of systemic sarcoidosis are diverse (see Table 3) Approximately one-third of patients present with vague constitutional symptoms such as fatigue, fever, nights sweats, and weight loss. 102 Pulmonary sarcoidosis is clinically and pathologically the most common manifestation of the disease.…”
Section: Systemic Manifestationsmentioning
confidence: 99%
“…4 Cutaneous sarcoidosis is the initial manifestation of the disease in nearly one-third of patients. 5 The skin (as well as the liver, spleen, and lymph nodes) is most often involved in African Americans. …”
Section: Introductionmentioning
confidence: 99%
“…Maña et al 5 identified the absence of erythema nodosum as a variable independently influencing activity persistence in sarcoidosis. Yanardag et al 6 found that the frequency of progressive disease was more significant in patients with specific cutaneous lesions. However, the prognostic significance of subcutaneous sarcoidosis because of the limited sample size in the studies has not been clearly established.…”
Section: To the Editormentioning
confidence: 99%
“…Ayrıca bu hastaları çoğunlukla ilk olarak değerlen-diren hekimler olan dermatologların, hastayı sistemik tutulum açısından değerlendirmesi önem arz etmektedir. Tanıda punch biyopsi oldukça kolay ve güvenilir bir yön-temdir (11). Ancak granülomatöz iltihap yapan diğer hastalıklar tüberküloz, atipik mikobakteri enfeksiyonları, fungal enfeksiyonlar, yabancı cisim reaksiyonları ve romatoid nodüller histopatolojik ayırıcı tanıda göz önünde bulundurulmalıdır (3,12).…”
Section: şEkil 6: Bilgisayarlı Toraks Tomografisinde Normal Akciğer Punclassified
“…Bu kapsamda muhtemel enfeksiyöz nedenleri dışlamak için alınan örneklerin spesifik ve nonspesifik kültürü, serolojik değerlendirme, tüberkülin testi, serum ACE düzeyi yardımcı olabilir. Özellikle spesifik deri tutulumu olan hastalarda ACE düzeyi belirgin olarak yüksek bulunmuştur (11). Bir çalışmada sarkoidoz deri tutulumu olan hastalar ile psöriyazis olguları karşılaş-tırılmış ve sarkoidozda ACE düzeyleri daha yüksek bulunmuştur (13).…”
Section: şEkil 6: Bilgisayarlı Toraks Tomografisinde Normal Akciğer Punclassified